Pore structure evolution and cracking mechanism of mortar caused by pore vapor pressure during microwave heating - Rujia Qiao; Zhoufenglin Lei; Yuan Yuan; Zhushan Shao; Shuailing Li; Hang Zhang; Tengfei Yang (Journal of Materials Research and Technology)
Utilizing microwave heating technology to crush concrete and recycle high-quality aggregates is the most promising concrete recycling technology currently. The essence of microwave-assisted concrete crushing operates by fracturing the mortar matrix. Increasing the moisture content of mortar is an important measure to improve microwave crushing efficiency, but the crushing mechanism needs further research. In this paper, microwave heating tests of mortar with different moisture content were carried out, and the effects of microwave power, heating duration and moisture content on the temperature, mass loss and pore structure evolution of mortar were obtained. It is found that there are two main effects in the microwave heating process: hydrothermal migration and pore vapor pressure cracking. The dominance of the two is significantly affected by microwave heating power and mortar water content. In order to explain the cracking mechanism caused by pore vapor pressure, a single-pore cracking model of mortar was established. The results show that the critical pore vapor pressure for cracking of mortar with initial crack is significantly lower than that for mortar without initial crack. The critical cracking pressure decreases by about 80 % (67 %) in the presence of penetrating crack (surface crack), respectively. This study establishes a theoretical connection between the critical pressure for mortar cracking and the microwave heating parameters. The results can provide theoretical guidance for the parameters optimization of the concrete crushing technology driven by microwave heating.